Synthesis and characterization of novel bio‐based epoxy polymers derived from natural phenolic compound. Issue 9 (13th December 2022) - Sudprasert, Pirada; Kariya, Shotaro; Ogino, Kenji; Chirachanchai, Suwabun; Kanehashi, Shinji
Abstract: Bio‐based epoxy polymer was prepared from cardanol derivatives, epoxy prepolymer and phenalkamine at room temperature without solvent. Chemical structures of cured epoxy polymers were analyzed by FT‐IR and 1 H NMR spectroscopy. The drying, physical, thermal, optical, and mechanical properties of the epoxy polymers were investigated in terms of the composition of epoxy and amine compounds, molecular weight of the epoxy prepolymer, and the effect of post‐curing process. The resultant epoxy polymers showed flexible nature, thermal stability (e.g., thermal decomposition temperature of 300°C). Furthermore, the epoxy polymers possessed the anti‐microbial activity against Escherichia coli and Staphylococcus aureus The molecular weight of the epoxy prepolymer also strongly affected the drying property, suggesting that the drying time can be controlled by the molecular weight of the prepolymer. Thermal treatment of the polymers as post‐curing was effective approach to improve the hardness, thermal stability, and mechanical strength. Hence, this cardanol derivatives‐based novel epoxy polymer can be expected as highly green functional epoxy polymers for coating, film and resin applications. Abstract : Novel bio‐based epoxy polymers derived from cashew nuts shell liquid (CNSL), natural phenolic compound.